2003
DOI: 10.1016/s0034-4257(02)00206-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure and influence of tropical river plumes in the Great Barrier Reef: application and performance of an airborne sea surface salinity mapping system

Abstract: Input of freshwater from rivers is a critical consideration in the study and management of coral and seagrass ecosystems in tropical regions. Low salinity water can transport natural and manmade river-borne contaminants into the sea, and can directly stress marine ecosystems that are adapted to higher salinity levels. An efficient method of mapping surface salinity distribution over large ocean areas is required to address such environmental issues. We describe here an investigation of the utility of airborne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Yet, remote sensing has a potential to offer more than localizing the distribution of seagrass meadows. Remote sensing may also be used to detect environmental conditions affecting seagrass status, such as the detection of sediment plumes (Burrage et al, 2003;Nezlin et al, 2005). In terrestrial systems remote sensing has been applied to detect concentrations of foliar nitrogen (Lilienthal et al, 2000;Mutanga et al, 2003;Ferwerda et al, 2005;Skidmore et al, 2005) and photosynthesis levels (Zhao et al, 2005) in plants.…”
Section: Monitoring Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, remote sensing has a potential to offer more than localizing the distribution of seagrass meadows. Remote sensing may also be used to detect environmental conditions affecting seagrass status, such as the detection of sediment plumes (Burrage et al, 2003;Nezlin et al, 2005). In terrestrial systems remote sensing has been applied to detect concentrations of foliar nitrogen (Lilienthal et al, 2000;Mutanga et al, 2003;Ferwerda et al, 2005;Skidmore et al, 2005) and photosynthesis levels (Zhao et al, 2005) in plants.…”
Section: Monitoring Requirementsmentioning
confidence: 99%
“…They found that the primary factors regulating the relationship between rainstorms and sediment plumes were watershed land-use characteristics, size, and elevation. Burrage et al (2003) used a prototype Scanning Low Frequency Microwave Radiometer (SLFMR) to describe the structure and extent of a river plume. The SLFMR was found to have sufficient precision (1 psu) and accuracy (3 psu) to provide a useful description of plumes emanating from estuaries of moderate discharge levels.…”
Section: Mapping Sediment Concentrations and Light Climatementioning
confidence: 99%
“…Airborne microwave radiometers have been used to determine the structure and influence of river plumes, since the input of freshwater plumes from rivers is a critical consideration in the study and management of coral and seagrass ecosystems (Burrage et al 2003;Burrage et al 2008;Wang, Heron, Hacker 2007). Low salinity water can transport natural and man-made river-borne contaminants into the sea, and can directly stress marine ecosystems that are adapted to higher salinity level.…”
Section: Microwave Radiometry and Sea Surface Salinitymentioning
confidence: 99%
“…In 2000, an instrument that is based on the prototype SLFMR [5], [11], [13] was constructed for an Australian research consortium by Quadrant Engineering (now ProSensing), Amherst, MA. The SLFMR instrument has been used in the study of the estuarine plume of the Herbert River in the Great Barrier Reef (GBR), and results on the structure and influence of tropical river plumes were obtained [3].…”
Section: Introductionmentioning
confidence: 99%
“…For the Australian SLFMR, the absolute accuracy of the instrument was empirically determined by using in situ observations with a conductivity-temperature-depth (CTD) probe, and it was found that the calibration with respect to groundtruth data drifted over a salinity range of 3 psu [3]. To improve the precision, a new-generation microwave radiometer was developed in 2004 based on the SLFMR and the STARRS radiometer technology.…”
Section: Introductionmentioning
confidence: 99%